The Role of the Family in Achieving Societal Security: A Field Study - Mesmar, Maen Fathi Abed (Journal of Ecohumanism, 2025)
This study aimed to know the role of the family in achieving societal security by knowing the degree of availability of the family's social, educational, and religious role in achieving societal security. The study relied on the descriptive-analytical approach. The study population consisted of workers in the community police departments in Jordan in the regions (North, Middle, and South), and a stratified random sample was selected; the number of its members was (150) respondents. The statistical package program (SPSS) was used to test the study's hypotheses. As a result, the study reached several results, the most important of which are: the trends of the study sample are favorable and with a high degree towards the level of availability of the role of the family (social, educational, religious); Where the most available dimension was the religious role of the family, which came in the first rank, followed by the dimension of the social role of the family in the second rank, and then the educational role of the family in the last rank, and the results showed the existence of a positive relationship with statistical significance and a high degree of influence for the role of the family in its dimensions (social, educational, religious) in achieving societal security.